1994
DOI: 10.1093/oxfordjournals.eurheartj.a060485
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up of the Oxford Cholesterol Study: assessment of the efficacy and safety of simvastatin in preparation for a large mortality study

Abstract: We report the results of a randomized single-centre study designed to assess the effects of simvastatin on blood lipids, blood biochemistry, haematology and other measures of safety and tolerability in preparation for a large-scale multicentre mortality study. Six hundred and twenty-one individuals considered to be at increased risk of coronary heart disease were randomized, following a 2-month placebo 'run-in' period, to receive 40 mg daily simvastatin, 20 mg daily simvastatin or matching placebo. Their mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
18

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 0 publications
4
48
2
18
Order By: Relevance
“…Studies that were excluded from any meta-analysis of clinical outcomes because they had not published such data in usable form were 4D, for which only preliminary data were available, indicating a nonsignificant reduction in the primary end-point of combined cardiac death, non-fatal MI and stroke, 104 and the Oxford Cholesterol Study, which collected data on the number of patients who suffered all-cause, CHD and other vascular mortality, non-fatal MI and stroke, but only published these data in an interim report which did not attribute such outcomes to treatment groups. 101 Mondillo 2003 did not report any clinical outcomes other than walking distances. 105 Many studies were also too small to show a statistically significant effect in relation to nonfatal outcomes.…”
Section: Assessment Of Effectiveness Of Statins: All Placebo-controllmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies that were excluded from any meta-analysis of clinical outcomes because they had not published such data in usable form were 4D, for which only preliminary data were available, indicating a nonsignificant reduction in the primary end-point of combined cardiac death, non-fatal MI and stroke, 104 and the Oxford Cholesterol Study, which collected data on the number of patients who suffered all-cause, CHD and other vascular mortality, non-fatal MI and stroke, but only published these data in an interim report which did not attribute such outcomes to treatment groups. 101 Mondillo 2003 did not report any clinical outcomes other than walking distances. 105 Many studies were also too small to show a statistically significant effect in relation to nonfatal outcomes.…”
Section: Assessment Of Effectiveness Of Statins: All Placebo-controllmentioning
confidence: 96%
“…These were the Aronow, Mohler and Mondillo studies in patients with intermittent claudication 21,105,118 and the Oxford Cholesterol Study in patients at increased risk of CHD because of a history of MI, angina pectoris, stroke, TIA, PAD, treated diabetes mellitus or treated hypertension. 101 The Mohler study specifically measured quality of life, using the Short-Form 36 (SF-36); it did not find any significant difference between treatment groups. 21 This study also used the Walking Impairment Questionnaire (WIQ) and the Low Level Physical Activity Recall (LOPAR) questionnaire.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…18 Typically with standard doses, little or no effect is seen on gamma glutamyl transferase, alkaline phosphatase and bilirubin. 19 , though a small percentage of patients experience an increase in liver enzymes like alanine and aspartate transaminase. 1 The increases in transaminase are seen within first six months of therapy with statins.…”
Section: Effects Of Statins On Livermentioning
confidence: 99%
“…The present results are supported by negative findings in a double-blind, placebo-controlled study of the effects of simvastatin and pravastatin on EEG and subjective sleep parameters in hyperlipidaemic patients [12], and in a double-blind, placebo-controlled study of EEG evoked potentials, mood, sleep and cognitive performance in healthy volunteers receiving a higher dose of simvastatin (40 mg day-) [4]. Also, there were no significant differences between simvastatin and placebo in Profile of Mood States scores in the 600 patient, double-blind, placebo-controlled, Oxford Cholesterol Study [13] (personal communication). On the basis of the current data it is concluded that these two chemically distinct HMG CoA reductase inhibitors, which are both effective in reducing LDL cholesterol, are without substantive effects on cognitive function as assessed by a range of psychometric procedures.…”
Section: Serum Lipid Effectsmentioning
confidence: 99%